Studi Kasus Kesalahan Penulisan Nama Kapal MT. Gloria Sentosa di Surat Persetujuan Berlayar (SPB) - Retnandari, Septina Dwi; Khaeroman, Khaeroman; Muhammad Edi Azmi (Jurnal Maritim Polimarin, 2023)
In the ship berthing process, ship documents are very important, especially the Sailing Approval Letter because it has a big impact on the smooth berthing of the ship and can affect the process of loading and unloading goods. Apart from that, this research discusses the factors that cause ships to be detained and the impact that ship detention has on the process of loading and unloading ships at the dock. This research is a descriptive type of research with data collection techniques in the form of observation, interviews and documentation with primary and secondary data sources. Data analysis uses qualitative techniques. The purpose of this research is to determine the impact of errors in writing the name of the ship on the Sailing Approval Letter on the smooth berthing of the ship at the destination port agented by PT. Bintang Samudra Utama. Factors that cause MT vessels. Gloria Sentosa was detained by the harbormaster because there was an error in writing the name of the ship on the Sailing Approval Letter and this had an impact on the loading and unloading process of the ship at the dock. The efforts made are that the Harbor Master and Master officers are more thorough in checking documents and the company must be more selective in choosing the ships that will be agented